Implementasi Mekanisme Kebijakan Penataan dan Pemerataan Tenaga Pendidik Jenjang SMP pada Disdik Kota Batu Berdasarkan Perwali Kota Batu No. 57/2025 - Aprillia, Nanda; Muchsin, Slamet; Ahmadi, Rulam (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The aim of the research is to determine the process, supporting factors and inhibiting factors in the implementation of policy mechanisms for structuring and equalizing teaching staff at Junior High School (SMP) level at the Batu City Education Office based on Batu Mayor Regulation Number 57 of 2015. This research uses descriptive qualitative research methods. This research was conducted at the Batu City Education Office, Junior High School (SMP) Development Division in May 2022-July 2023. Data collection techniques were carried out using interview, observation and documentation techniques. The data analysis technique used is a qualitative technique consisting of data collection, data reduction, data presentation and drawing conclusions. The results of the research show that 1) the process implementation results for the mechanism for structuring and equalizing teaching staff at the Junior High School (SMP) level at the Batu City Education Office is in accordance with Batu Mayor Regulation Number 57 of 2015. 2) The implementation of the policy on the mechanism for structuring and equalizing teaching staff at the Junior High School (SMP) level at the Batu City Education Office is going well and in accordance with Batu Mayor Regulation Number 57 of the Year thanks to the existence of supporting factors both internal and external. c) In its implementation there are also obstacles caused by inhibiting factors both internal and external.